National investment programs and sustainable development - Paulina Szyja (Economic and Environmental Studies (E&ES), 2014)
In situation of economic crisis many countries, for example the United States, members of European Union prepared anti-crisis programs to conduct investments. In most cases, they concentrated on modernization of transport or energy infrastructure. In Poland it would have been presented program "Polish Investments". The main purposes of the article is presentation of public investments programs and their role in sustainable development.
Keywords: 330; investments; anti-crisis programs; environment; sustainable development